2009
DOI: 10.1177/019874290903500101
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Instructional Methods for Teaching Math Skills to Secondary Students with Emotional/Behavioral Disorders

Abstract: The purpose of this study was to determine the most effective of three instructional methods for teaching mathematics to secondary students with emotional and behavioral disorders. A single-subject alternating-treatments research design was used to compare three instructional methods: direct teach, computer-assisted instruction, and a combination of both methods. Disability label, age, and IQ were related to learning outcomes. In addition, although the combined method was more effective for some learners, vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 11 publications
1
31
1
Order By: Relevance
“…Results of this study seem to contradict findings from Hott et al (2014) and Billingsley, Scheuermann, and Webber (2009). Many students in the first study benefited from peer tutoring and self-monitoring; however, a functional relationship between those interventions and improved academic outcomes did not exist for all students.…”
Section: Discussioncontrasting
confidence: 87%
“…Results of this study seem to contradict findings from Hott et al (2014) and Billingsley, Scheuermann, and Webber (2009). Many students in the first study benefited from peer tutoring and self-monitoring; however, a functional relationship between those interventions and improved academic outcomes did not exist for all students.…”
Section: Discussioncontrasting
confidence: 87%
“…However, the type of SEN should not be the sole indicator when planning instructional/pedagogic practices, as individual characteristics and variation are also of paramount importance. For example, Billingsley, Scheuermann and Webber () in comparing three instructional practices for teaching mathematics to students with emotional and behavioural difficulties found that no single method was preferable for all students but results varied across individuals based on other variables such as age, number of years spent at school and the existence of additional learning difficulties among others. This paper has also shown that the self‐efficacy of students with SEN is overall lower compared to students without SEN. Qualitative results revealed how this is closely linked to students’ mathematical dispositions.…”
Section: Preliminary Discussion and Conclusionmentioning
confidence: 99%
“…In four studies, the researcher conducted training for the intervention and the teacher carried out the instruction. Authors of three studies (Haydon et al, 2012;Stowitschek, Lewis, Shores, & Ezzell, 1980) provided details on the training of the interventionist, while authors of seven studies (Billingsley, Scheuermann, & Webber, 2009;Bottge et al, 2006;Cade & Gunter, 2002;Carr & Punzo, 1993;Davis & Hajicek, 1985;Hawkins, Brady, Hamilton, Williams, & Taylor, 1994;Haydon et al, 2012) described the background of the interventionist (e.g., years of teaching and certification area). *5 Practice standard potentially included but more information needed to be certain.…”
Section: Nature Of the Interventionist And Intervention Focusmentioning
confidence: 99%
“…This category included studies that incorporated video-based anchors, computer-assisted instruction, and iPads into instruction. Three studies included the following technology based interventions: (a) Enhanced Anchored Instruction (EAI) using video-based anchors that embedded real-world situations into instruction (Bottge et al, 2006), (b) computer-assisted instruction with use of a self-paced math software program with assessment features (Billingsley et al, 2009), and (c) iPads (Haydon et al, 2012).…”
Section: Technology-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation